Pathological circuit function underlying addiction and anxiety disorders - Luthi, Andreas; Luscher, Christian (Nature neuroscience, 2014)
In this Review, Lüscher and Lüthi draw some parallels between anxiety and addiction disorders as diseases of the brain's emotional valence system. The authors present an update on the anatomy and heterogeneity of the fear and reward circuitries, analyze our understanding of the synaptic and cellular mechanisms thought to underlie the two conditions and discuss recent studies causally linking the resulting circuit dysfunctions and alterations in behavior. Current models of addiction and anxiety stem from the idea that aberrant function and remodeling of neural circuits cause the pathological behaviors. According to this hypothesis, a disease-defining experience (for example, drug reward or stress) would trigger specific forms of synaptic plasticity, which in susceptible subjects would become persistent and lead to the disease. While the notion of synaptic diseases has received much attention, no candidate disorder has been sufficiently investigated to yield new, rational therapies that could be tested in the clinic. Here we review the arguments in favor of abnormal neuronal plasticity underlying addiction and anxiety disorders, with a focus on the functional diversity of neurons that make up the circuits involved. We argue that future research must strive to obtain a comprehensive description of the relevant functional anatomy. This will allow identification of molecular mechanisms that govern the induction and expression of disease-relevant plasticity in identified neurons. To establish causality, one will have to test whether normalization of function can reverse pathological behavior. With these elements in hand, it will be possible to propose blueprints for manipulations to be tested in translational studies. The challenge is daunting, but new techniques, above all optogenetics, may enable decisive advances.